Quando o anjo do extermínio se aproxima de nós: representações sobre o cólera no semanário cratense O Araripe (1855-1864) - Alexandre, Jucieldo Ferreira (2010)
This work belonging to the line of research of Regional History in the Post Graduation Program in History of the Federal University of Paraíba, within the area of Historic Culture has as objective to discuss the representations engendered by the weekly newspaper O Araripe printed in the city of Crato, region of Cariri in the south of the Province of Ceará, under the orientation of a group of market traders and liberal professionals of that city, connected to the Liberal Party to refer to a disease: the cholera. The period chosen starts in 1855, the year of the foundation of the referred newspaper and of the arrival of the cholera to the Brazilian territory, and ends in 1864, when the second and last outbreak of this disease happens in the 19th century Crato and before the last year of circulation of the newspaper. This dissertation has as inspiration the Historiography of Diseases, mainly developed in the last decades of the 20th century, due to the dialogue between History and other disciplines such as Sociology and Anthropology. The studies developed by this historiography have shown how the phenomenon of the diseases exceeds the domain of the natural, in that they are experienced from many different contexts and spaces, being socio-culturally interpreted by the historical subjects that start multiple representations and practices with the purpose to attribute meaning to these.